Oriental mythology - Campbell, Joseph 1904-1987; Deshanti A. Mckoy; Makayla S. Johnson; Makiah D. Johnson (Novato, California New World Library, 2021)
"In the second of a four-volume series, mythologist Joseph Campbell traces the evolution of world mythology as it developed into the distinctive religions of the Middle East, India, China, and Japan"--
Includes bibliographical references and index
Keywords: Mythology, Asian; Asia -- Religion